Effects of new logistics services on restaurants' business model and strategy - Vlassis, Nikolaos (2016)
The restaurant industry is present in every part of the world and has been a subject of significant interest for academic scholars. Despite being a more stable industry, technological innovations have started to reach restaurants as well. The purpose of this research is to study and analyze one of these innovations introduced to the full-service restaurant industry. Traditional delivery services in the restaurant industry have been acting as agents between restaurants and customers with the restaurants being in charge of the delivery. However, the food logistics service providers examined in this study offer their restaurant partners‟ new services such as control of the delivery process and co-marketing campaigns. More specifically, the research analyses the benefits and risks of this new service for the restaurant partners and how their business model and strategy is affected by partnering with food logistic service providers. Additionally, the effects of this new innovative service on the restaurant industry are reviewed. The study follows a qualitative method with a multiple case research design. During the data collection phase 15 case firms were interviewed in Helsinki, Finland. In order to accomplish a comprehensive approach on the topic and ensure the integrity of the study, the author analyzed all the sub-topics of the research by considering the viewpoint of both partnering sides. The collected data was categorized and analyzed through the content analysis method. The analysis revealed several interesting findings. The advantages of the new technology could be characterized as the most predictable findings of the study since the main objective of the partnership is quite plain. Both partnering sides agreed that increased revenue and free marketing/visibility are the main benefits of the partnership for the restaurant partners, with deviation mostly on the underlying reasons of why the partnership is beneficial to them. On the contrary, the analysis of the disadvantages and risks revealed differences between the viewpoints of the partners. Restaurant owners were mainly concerned about customer satisfaction and identified product and service quality as the main risk of the partnership. This is an interesting topic as it can be an indicator of possible misalignment of incentives between the business partners in the future. Moreover, the results confirmed the fact that this new technology has certainly affected the business model and strategy of most of the restaurants that have chosen to partner with food logistic service providers. Restaurants have modified their operations and strategy to meet the „needs‟ of the new service. Finally, the new technology has provided the restaurants with a new ground to compete in and has reformed some of the traditional „rules‟ of the full-service restaurant industry.